PENGARUH PENGGUNAAN MEDIA AUDIOVISUAL BERBASIS YOUTUBE TERHADAP HASIL BELAJAR MATEMATIKA PADA PESERTA DIDIK - Iza Azkia Rahma Wijaya; Usep Saepul Mustakim; Ismi Widyaningrum (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
This study aims to analyze the effect of using Youtube-based audiovisual media on students' mathematics learning outcomes. Youtube-based audiovisual media is considered to be an effective alternative because it is able to present visualizations and animations that facilitate understanding. This study uses a quantitative method with a quasi-experimental design with pre-test and post-test techniques. The research sample consisted of two groups, namely the experimental group using Youtube media and the control group using conventional learning methods. The results of the study showed that there was a significant effect of using Youtube-based audiovisual media on students' mathematics learning outcomes. The experimental group using Youtube media showed a higher increase in learning outcomes compared to the control group. These findings indicate that using Youtube as a learning medium can effectively improve students' understanding of mathematical concepts.